Преобразовать уравнения используя второе свойство равенств. (х-1):3=(20-2х):3 15*(е+2):7=6*(2е+7):7
Преобразовать уравнения используя второе свойство равенств. (х-1):3=(20-2х):3 15*(е+2):7=6*(2е+7):7
Ответ(ы) на вопрос:
[latex]\frac{x-1}{3}=\frac{20-2x}{3}\\ \frac{x-1}{3}*3=\frac{20-2x}{3}*3\\ x-1=20-2x\\ 3x=21\\ \frac{3x}{3}=\frac{21}{3}\\ x=7\\ \\ \frac{15*(e+2)}{7}=\frac{6*(2e+7)}{7}\\ \frac{15*(e+2)}{7}*7=\frac{6*(2e+7)}{7}*7\\ 15*(e+2)=6*(2e+7)\\ 15e+30 = 12e + 42\\ 3e = 12\\ \frac{3e}{3} = \frac{12}{3}\\ e = 4 [/latex]
Не нашли ответ?
Похожие вопросы